Case of successful hybrid revascularization and limb salvage in patient with CLI after multiply ABF thrombosis and absence of outflow arteries - A. F. Kharazov; V. M. Luchkin; N. M. Basirova; V. A. Kulbak; A. I. Maslov («REMEDIUM GROUP» Ltd., 2020)
Patients with CLI often present multilevel disease. They underwent multiply revascularization procedures aiming to save thelimb. The main obstacle is absence or poor outflow arteries. Inability to restore bloodflow usuallyleads to ischemia progression and consequent amputation. We describe two cases of successful treatment of patient with CLI after multiply ABF thrombosis and absence of outflow arteries.The first 63 years old patient developed the third case of ABF thrombosis as a result of profunda and superficial femoral arteries chronic occlusion. We performed mechanical recanalization and angioplasty of anterior tibial, popliteal, subintimal recanalization and angioplasty of superficial femoral arteries. After that the ABFleg was sutured to subintimal space of femoral artery. The next case was another 63 years old patient with total chronic occlusion of iliac, femoral, popliteal and tibioperoneal trunk. We performed mechanical recanalization and angioplasty of anterior tibial, popliteal, subintimal recanalization and angioplasty of superficial femoral arteries. And then extra anatomy femoro-femoral autovenous bypass, distal anastomosis was performed by using subintimal artery space also. Thelong term period was 27 months for the first case and 20 months - for the second one. All bypasses were patient.Therefore this described above approach of hybrid open and endovascular surgery could give additional chance forlowlimb revascularization in this so-called hopeless group with criticallimb ischemia.